2013
DOI: 10.1021/es3047334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Humic Acid on Titanium Dioxide Nanoparticle Toxicity to Developing Zebrafish

Abstract: Titanium dioxide nanoparticle (TiO2NP) suspension stability can be altered by adsorption of dissolved organic matter (DOM). This is expected to impact their environmental fate and bioavailability. To date, the influence of DOM on the toxicity of TiO2NPs to aquatic vertebrates has not been reported. We examined the impact of Suwannee River humic acid (HA) on the toxicity of TiO2NPs to developing zebrafish (Danio rerio) in the dark and under simulated sunlight illumination. Adsorption of HA increased suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 54 publications
3
87
0
1
Order By: Relevance
“…At the nanoscale, the refractive index of TiO 2 NPs is even higher; therefore, it is also used in sunscreens and cosmetics as well as paints, varnishes, and coatings (Hendren et al, 2011). The adsorption of HA increased TiO 2 NP stability in suspension, and TiO 2 NPs were more toxic in the presence of HA (Yang et al, 2013). It was demonstrated that the aggregation of TiO 2 NPs is dependent on the presence and copresence of NOM (0.2-41.1 mg/L DOC), the pH of the solution, as well as other properties, such as the IS of the solution and the presence of relevant monovalent and divalent ions (Ottofuelling et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the nanoscale, the refractive index of TiO 2 NPs is even higher; therefore, it is also used in sunscreens and cosmetics as well as paints, varnishes, and coatings (Hendren et al, 2011). The adsorption of HA increased TiO 2 NP stability in suspension, and TiO 2 NPs were more toxic in the presence of HA (Yang et al, 2013). It was demonstrated that the aggregation of TiO 2 NPs is dependent on the presence and copresence of NOM (0.2-41.1 mg/L DOC), the pH of the solution, as well as other properties, such as the IS of the solution and the presence of relevant monovalent and divalent ions (Ottofuelling et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…small size, surface activity, chemical composition and photocatalytic activity, the water chemistry, such as pH, ionic strength and natural organic matters (NOM), are also non-negligible factors to understand the uptake and toxicity of TiO 2 NPs to aquatic organisms (Von der Kammer et al 2010). Previous research report the influence of humic acid (HA) on toxicity of TiO 2 NPs toward developing zebrafish, indicating that adsorption of HA increased suspensions stability and decreased TiO 2 NPs exposure, and TiO 2 NPs showed higher toxicity in the presence of HA (Yang et al 2013). Moreover, it has been proved that HA can increase the surface negative charges and reduce the aggregation of graphene, and then regulate (Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the body distribution, metabolism, and excretion of NPs are poorly understood and hampered by a lack of methods for measuring NPs in tissues. It remains possible that TiO 2 NPs could interfere or stimulate stress responses in fish (Menard et al 2011;Clemente et al 2013;Yang et al 2013), which was shown as oxidative response. However, the oxidative response could be caused by direct (primary) or indirect (secondary) effect by NPs or its released ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the environment, BDE-209 can also interact with other substances. In this regard, nanoparticles (NPs) have basic physicochemical properties that include high insolubility and a large surface area to volume ratio, which indicate that they are likely to interact with other substances in surface waters (Handy et al, 2008;Yang et al, 2013). Thus, the interaction between BDE-209 and NPs may further modify the environmental behavior and/or toxicity of BDE-209, and such interactions are therefore of particular concern for environmental risk assessments.…”
Section: Introductionmentioning
confidence: 99%